Differentiation under capitalism: Genesis and consequences of the rent gap. (October 2021) - Liu, Cheng; Deng, Yu; Song, Weixuan; Wu, Qiyan; Gong, Jian
Uneven development theory and its corollary (i.e. rent-gap theory) are either excessively general or insufficiently flexible to expound the variations of gentrification with unique historical trajectories. A representative example is education-led gentrification in China. The lacuna restricts the explanatory power of rent-gap theory and justifies the fault line between the rent gap and two important phenomena: the forms of displacement identified by Marcuse and territorial stigmatisation. This paper recasts Neil Smith's insights about uneven development from two perspectives, temporal and social differentiations, and elaborates how the interplay between both differences engenders territorial stigmatisation and displacement. Moreover, as two diametrically opposed phenomena, territorial glorification (e.g. super-gentrification and education-led gentrification) and territorial stigmatisation are simultaneously situated in one framework, which is evaluated in education-led gentrification in Nanjing. Redirecting the empirical research from global cities to less established but more representative urban centres, this research shows the potentially wide applicability of the theoretical framework.